Non-glycosylated IGF2 prohormones are more mitogenic than native IGF2 - Potalitsyn, Pavlo; Mrázková, Lucie; Selicharová, Irena; Tencerová, Michaela; Ferenčáková, Michaela; Chrudinová, Martina; Turnovská, Tereza; Brzozowski, Andrzej Marek; Marek, Aleš; Kaminský, Jakub; Jiráček, Jiří; Žáková, Lenka (Communications biology, 2023)
Insulin-like Growth Factor-2 (IGF2) is important for the regulation of human embryonic growth and development, and for adults' physiology. Incorrect processing of the IGF2 precursor, pro-IGF2(156), leads to the formation of two IGF2 proforms, big-IGF2(87) and big-IGF2(104). Unprocessed and mainly non-glycosylated IGF2 proforms are found at abnormally high levels in certain diseases, but their mode of action is still unclear. Here, we found that pro-IGF2(156) has the lowest ability to form its inactivating complexes with IGF-Binding Proteins and has higher proliferative properties in cells than IGF2 and other IGF prohormones. We also showed that big-IGF2(104) has a seven-fold higher binding affinity for the IGF2 receptor than IGF2, and that pro-IGF2(87) binds and activates specific receptors and stimulates cell growth similarly to the mature IGF2. The properties of these pro-IGF2 forms, especially of pro-IGF2(156) and big-IGF2(104), indicate them as hormones that may be associated with human diseases related to the accumulation of IGF-2 proforms in the circulation.
Keywords: Adult; Cell Proliferation; insulinu podobný růstový faktor II; Intercellular Signaling Peptides and Proteins; proliferace buněk; dospělí; Cell Cycle; Insulin-Like Growth Factor II; Mitogens; mezibuněčné signální peptidy a proteiny; Humans; buněčný cyklus; lidé; mitogeny